Representation of Mother's Role in the Family in the Movie "Dua Hati Biru" - Baelqis Yasminagara; Andika Sanjaya (Jurnal Dakwah dan Komunikasi, 2025)
The purpose of this research is to find out the hidden signs and meanings behind the film "Dua Hati Biru" in presenting the role of a mother. The theory used in this research is Roland Barthes' semiotics. The paradigm in this study is a critical paradigm, this approach uses qualitative with Roland Barthes' semiotic method. This research is an analysis by observing images and dialogues that contain elements of the representation of the mother's role. The results that will be obtained are shown through the scenes in the film "Dua Hati Biru". This representation of the mother's role is found starting from a mother who takes care of children, home, work and when overcoming problems in the household.